Making sense of a most popular metaphor in management: Towards a HedgeFox Scale for cognitive styles - Timo Meynhardt; Carolin Hermann; Stefan Anderer (Administrative Sciences, 2017)
Research on cognitive style has gathered momentum over the past 40 years, especially with respect to learning, problem-solving, and decision-making. This investigation adapts Tetlock's hedgehog-fox scale for German-speaking respondents through three large-scale studies (n = 17,072) and examines the influence of cognitive style on employees' public value assessments of their employing organizations. Our data led us to propose a revised and more economical HedgeFox Scale. In contrast with Tetlock's findings, our results provide empirical and theoretical arguments for a two-factor structure. This shift in dimensionality affects the nature of the construct and aligns hedgehog-fox research with the latest developments in cognitive style research. Our results contribute to the ongoing interest in the dimensionality of cognitive styles and support the call for a more diverse picture. Finally, we provide recommendations for individuals and organizations.
Keywords: 350; decision making; cognition; cognitive style; dimensionality; hedgehog-fox metaphor; public value